Development of a human wrist joint rehabilitation robot with AFC-PID control - Abbas Moloody; Mohammad Mahjoob; Azizan As’arry; Mohd Zarhamdy Mohd Zain (National Research and Innovation Agency, 2026)
Robotics is transforming healthcare rehabilitation by improving precision, efficiency, and accessibility. While industrial robots are widely used, service robots in medical applications remain underutilized. Wrist rehabilitation is essential for restoring mobility and strength after injury or surgery. This study presents a three degrees of freedom (DOF) robotic system designed to assist patients with wrist mobility impairments, aiming to enhance rehabilitation outcomes. This study develops a 3-DOF wrist rehabilitation robot with active force control – proportional-integral-derivative (AFC-PID) control to enhance rehabilitation outcomes. Traditional rehabilitation methods for wrist impairments are time-consuming, physically demanding, and inconsistent. Patients require structured therapy to reduce stiffness, receive corrective assistance for incomplete movements, and strengthen muscles. The limitations of conventional treatments create a need for more efficient and accessible therapeutic solutions. The robotic system operates in three phases: phase 1 (passive mode) where the robot aids wrist movement to relax muscles, phase 2 (assisted mode) where the robot provides compensatory force for incomplete movements, and phase 3 (strengthening mode) where the robot applies resistance to build muscle strength. The robot operates in passive, assistive, and resistive modes. Force-sensitive resistor (FSR) sensors measure interaction forces, and control is implemented via ATMEGA 32 microcontroller. Simulation and experimental trials with male and female participants were conducted. A microcontroller regulates the torque, force, angular acceleration, angular velocity and angular magnitude and direction using a PID control strategy, which is applied in accordance with therapeutic protocols. Experimental results demonstrate that the system effectively reduces stiffness, assists movement completion, and strengthens muscles through controlled resistance. The robot achieves maximum torque of 1.00 N·m, angular velocity 0.55 rad/s, and high repeatability (intraclass correlation coefficient (ICC) b 0.98 . Mode C shows active engagement with performance approaching reference values. Automating rehabilitation improves treatment efficiency and accessibility, offering a promising solution for patient recovery. The system provides adaptive, reliable, and gender-independent wrist rehabilitation, demonstrating clinical potential. The developed 3-DOF wrist rehabilitation robot with AFC-PID control achieves a maximum torque of 1.00 N·m, angular velocity of 0.55 rad/s, and reduces perceived joint stiffness by up to 15 %, demonstrating precise, adaptive assistance across passive, assistive, and resistive modes.